MSME Financial Administration Management Training in Argomulyo Village, Sepaku District, North Penajam Paser Regency - Miswaty Miswaty; Didik Hadiyatno; Hairul Anam; Misna Ariani; Dwi Susilowati; Wiwik Saraswati; Winda Lestari; Tutik Yuliani; Henny Oktapiyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
Financial management training in Argomulyo Village, Sepaku District, North Penajam Paser Regency. The article aims to provide understanding and improve the skills of the MSME group regarding calculating, recording, bookkeeping and managing business finances so that their businesses can develop further, thereby having an impact on increasing the skills of the Argomulyo Village MSME group regarding calculations and recording. and bookkeeping and financial management so as to improve MSME business and have an impact on increasing competitiveness and community welfare. This activity was carried out through training and mentoring, starting with a survey of training participants which showed that the majority of MSME owners had not separated business assets from personal assets. Training is carried out by providing worksheets that have been designed to be filled out by training participants so that participants can use them to record and calculate each participant's business finances. It is hoped that the results of the training can improve business financial management skills better. Based on the calculations they prepare during the training, they can be examples for participants to carry out in their business practices and they can also determine selling prices, develop investment plans and increase appropriate sources of funds so that they are expected to have an impact on increasing income and developing the business to be more advanced.